THE EFFECT OF QANÂ’AH ON THE TENDENCY TOWARD BODY DYSMORPHIC DISORDER AMONG SANTRI AT PESANTREN ANNUQAYAH LATEE II - Hikmatul Maulidiah; Nuzulul Khair (Living Sufism: Journal of Sufism and Psychotherapy, 2026)
Tendencies toward body dysmorphic disorder are a common phenomenon, particularly among females. This study aims to examine the effect of qanaah attitudes on the tendency toward body dysmorphic disorder among students at Annuqayah Latee II Islamic Boarding School. This research employs a quantitative approach with a correlational design. The sample consisted of 47 students selected using purposive sampling techniques. The research instruments used were the body dysmorphic disorder scale based on Phillips’ theory and the qanaah scale based on Buya Hamka’s theory. The results showed no significant effect between qanaah attitudes and tendencies toward body dysmorphic disorder (Sig. 0.256 > 0.05). The contribution of qanaah attitudes to body dysmorphic disorder tendencies was only 2.9%, indicating that other factors play a more dominant role. These findings provide important implications for developing Sufi and psychotherapy approaches to address body perception issues.